2011
DOI: 10.1007/978-3-642-19805-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Ordinal Theory for Expressiveness of Well Structured Transition Systems

Abstract: Abstract. To the best of our knowledge, we characterize for the first time the importance of resources (counters, channels, alphabets) when measuring expressiveness of WSTS. We establish, for usual classes of wpos, the equivalence between the existence of order reflections (nonmonotonic order embeddings) and the simulations with respect to coverability languages. We show that the non-existence of order reflections can be proved by the computation of order types. This allows us to solve some open problems and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The characterization of the expressive power by means of covering languages has been done for Petri nets (studied in the book of Peterson [27]), and more recently, for Well Structured Transition Systems (WSTS) [28] and for monotonic extensions of Petri nets like reset-transfer Petri nets, ν-Petri nets, unordered Petri nets [29,30]. More properties are decidable for VASS covering languages than for VASS reachability languages.…”
Section: Expressivenessmentioning
confidence: 99%
“…The characterization of the expressive power by means of covering languages has been done for Petri nets (studied in the book of Peterson [27]), and more recently, for Well Structured Transition Systems (WSTS) [28] and for monotonic extensions of Petri nets like reset-transfer Petri nets, ν-Petri nets, unordered Petri nets [29,30]. More properties are decidable for VASS covering languages than for VASS reachability languages.…”
Section: Expressivenessmentioning
confidence: 99%
“…Lpν¡N etsq LpDN q has been proved using an application of ordinal theory [29] as a measure of the state space that has to be explored to solve coverability in the corresponding models. The method used in [29] based on order reflection is a generalization of the strict inclusion between Lossy Channel Systems and CMRS proved in [6]. Furthermore, in [6] it has been shown that…”
Section: Expressivenessmentioning
confidence: 99%
“…Finer grained comparisons between AWN, νNets and (fragments of) Data nets are presented in [29]. More general models of Petri nets with data are presented in [89].…”
Section: Expressivenessmentioning
confidence: 99%
“…The strict inclusion Lpν¡N etsq LpDN q has been proved using an application of ordinal theory [29] as a measure of the state space that has to be explored to solve coverability in the corresponding models. The method used in [29] based on order reflection is a generalization of the strict inclusion between Lossy Channel Systems and CMRS proved in [6]. Furthermore, in [6] it has been shown that LpDN q LpCM RSq LpM SRpIdqq…”
Section: Expressivenessmentioning
confidence: 99%